PERANAN MANAJEMEN RANTAI PASOK DALAM MENINGKATKAN STRATEGI KOMPETITIF UMKM DI SAMARINDA - Rina masitoh, Catur Kumala Dewi (RJABM (Research Journal of Accounting and Business Management), 2018)
Small and medium trade will be displaced from the AFTA and Free Trade competition if it does not implement an effective and efficient supply chain. This is a major problem for Small and Medium Enterprises (SMEs) which indicate they have limitations in business capital, not or have not implemented technology and there is no formula for the objectives to be achieved by Micro, Small and Medium Enterprises (UMKM) and lack of resources human power in the form of expertise and skills of Micro, Small and Medium Enterprises (UMKM).The purpose of this study is to find out the model of supply chain from UMKM in Samarinda. An effective model of supply chain will provide an increase in UMKM competitiveness strategies. The effective supply chain strategy will give UMKM excellence in terms of price, quality, standard products and delivery time and customer service.The analysis technique used in this study is descriptive qualitative, namely by the stage of collecting and recording data, reducing data, presenting data, processing and drawing conclusions. This is done to describe the state of the object being examined based on the facts in the field, so that accurate and systematic data can be obtained. Data is obtained by observation, distribution of questionnaires. The population of this study is all UMKM in 25 sub-districts in Samarinda. Sampling using purposive sampling method where 9 sub-districts were taken by UMKM in Samarinda